Faktor Yang Mempengaruhi Mahasiswa Universitas Islam 45 Dalam Bertransaksi Menggunakan Rekening Bank Syariah - Ilda Alfiah; Rafika Rahmawati (At-Tamwil: Journal of Islamic Economics and Finance, 2023)
This study aims to determine the factors that influence consumer behavior, namely the influence of motivation and lifestyle on students' interest in transacting using Islamic bank accounts. The research method used in this study is quantitative with primary data sources through several data collections, namely pre-survey, questionnaire, and data archive. The population used in this study were students of the Islamic University 45 Bekasi class of 2018. The data analysis technique used through validity and reliability tests, classic assumption tests such as normality tests, multicollinearity tests and heteroscedasticity tests, then multiple linear regression analysis, coefficient of determination, as well as hypothesis testing through the F test and T test. This study shows that on the F test motivation and lifestyle simultaneously have a significant effect on students' interest in transacting using Islamic bank accounts. The results of the analysis on the T test, the motivation variable partially has a significant effect on students' interest in transacting using an Islamic bank account, but the lifestyle variable does not have a partial significant effect on students' interest in transacting using an Islamic bank account. Motivation is the variable that has the most influence or is more dominant in influencing students' interest in transacting using Islamic bank accounts.